MODEL PEMBELAJARAN THINK TALK WRITE (TTW) DAN TWO STAY TWO STRAY (TSTS) DALAM MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA - Embang Mawati (FKIP UNIVERSITAS PAKUAN, 2020)
LEARNING MODELS THINK TALK WRITE (TTW) AND TWO STAY TWO STRAY (TSTS) IN IMPROVING STUDENT BIOLOGY LEARNING OUTCOMESThis research is a class action research. The purpose of this research is to improve the learning outcomes of biological material, viruses and protists. The study was conducted in September-November 2018 in class X SMAN 1 Caringin 2018/2019 school year with a total of 36 students. The action research process is carried out in two cycles, each cycle consisting of four stages namely planning, implementing, observing / observing and reflecting. The end of each cycle is carried out tests with instruments that have been validated and tested for reliability. This research involves researchers, observers and the object under study. Based on observations before the research was conducted, the value of student learning outcomes in the last 2 years which reached the Minimum Mastery Criteria (KKM) was only 58.53% and 53.66% after classroom action research using the Think Talk Write (TTW) and Two models Stay Two Stray (TSTS), the value of the Biology learning outcomes of students in cycle I was 72.22% and increased to 82.93% in cycle 2. The attitudes learning outcomes after taking action in cycle I attitudes learning outcomes increased by an average of an average of 74.83 with a percentage of 69.44%, in cycle 2 attitudes learning outcomes increased to 77.67 with a percentage of attainment attitudes 78.05%. The results of learning skills in cycle 1 reached 74.92 with a percentage of achieving 80.55% skills, in cycle 2 the results of learning skills increased to 78.02 with a percentage of achievement of 86.11%. Based on the results achieved, this study produces the conclusion that by using Think Talk Write (TTW) and Two Stay Two Stray (TSTS) Learning Models can Improve Biological Learning Outcomes of Grade X students of SMAN 1 Caringin.